Fourier Transform Infrared and Raman Spectra of Metal Halide Complexes of 3,5-Lutedine in Relation to Their Structures - Yurdakul, Şenay; Davies, J. Eric D.; AKYÜZ, SEVİM (My University, 1996)
Fourier transform infrared (4000-200 cm) and Raman (3500-50 cm) spectra are reported for metal(II) halide 3,5-lutidine (3,5-dimethylpyridine) complexes of the following stoichiometries: M(3,5L)4X2 M=Co or Ni, X=C1 or Br; M=Mn or Cu, X=Br; M=Cd, X=I; M(3,5L)3X2 M=Fe, X=C1; M=Cu, X=Br; Hg(3,5L) X2 X=C1 or Br.Vibrational assignments are given for all the observed bands. Some structure- spectra correlations are found. For a given series of isomorphous complexes the sum of the difference between the liquid and ligand values of the vibrational modes of 3,5-lutidine is found to increase in the order of the second ionization potentials of the metals. The frequency shifts are also found to depend on the halogen.